Patterns in Child Phonology - Johnson, Wyn (Edinburgh University Press, 2022)
This advanced introduction to non-disordered phonological acquisition is the first textbook of its kind. Relevant to theoretical, applied and clinical phonology, this student-friendly text will enable the reader to enhance their observational skills and develop an understanding of the connection between child data and phonological theory. The authors provide a clear overview of issues in phonological acquisition, investigating child phonological patterns, phonological theory, the pre-production stages of phonological acquisition and non-grammatical factors affecting acquisition.Wyn Johnson and Paula Reimers first present a rich set of cross-linguistic data calling for phonological analyses before introducing a broad spectrum of phonological theory, which ranges from defining what is meant by 'markedness' to demonstrating how Optimality Theory explains child patterns. The question of when acquisition begins in the child also entails an investigation of pre-production stages, which casts doubt on the validity of phonological theory and necessitates the examination of alternative accounts of child patterns. By steering the reader to investigate the extent to which theories of speech production can explain recurring sound patterns in child language and introducing perceptual aspects of acquisition, this book provides readers with a sound understanding of the processes in phonological acquisition, essential to students and practitioners.Patterns in Child Phonology isData rich - with numerous and cross-linguistic child production dataTheory rich - pre-production stages of acquisition are examined and the book remains theory neutralStudent-friendly - includes definitions of phonological terms and concepts
Description based on online resource; title from PDF title page (publisher's Web site, viewed 29. Mrz 2022)
Keywords: Language & Linguistics; LANGUAGE ARTS & DISCIPLINES / General; Grammar, Comparative and general -- Phonology; Language acquisition